Targeting Oxidative Stress with Polyphenols to Fight Liver Diseases - Ivo F. Machado; Raul G. Miranda; Daniel J. Dorta; Anabela P. Rolo; Carlos M. Palmeira (MDPI AG, 2023)
Reactive oxygen species (ROS) are important second messengers in many metabolic processes and signaling pathways. Disruption of the balance between ROS generation and antioxidant defenses results in the overproduction of ROS and subsequent oxidative damage to biomolecules and cellular components that disturb cellular function. Oxidative stress contributes to the initiation and progression of many liver pathologies such as ischemia-reperfusion injury (LIRI), non-alcoholic fatty liver disease (NAFLD), and hepatocellular carcinoma (HCC). Therefore, controlling ROS production is an attractive therapeutic strategy in relation to their treatment. In recent years, increasing evidence has supported the therapeutic effects of polyphenols on liver injury via the regulation of ROS levels. In the current review, we summarize the effects of polyphenols, such as quercetin, resveratrol, and curcumin, on oxidative damage during conditions that induce liver injury, such as LIRI, NAFLD, and HCC.